If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8n-10+2n+3=n+4+3(2n-1)
We move all terms to the left:
8n-10+2n+3-(n+4+3(2n-1))=0
We add all the numbers together, and all the variables
10n-(n+4+3(2n-1))-7=0
We calculate terms in parentheses: -(n+4+3(2n-1)), so:We get rid of parentheses
n+4+3(2n-1)
determiningTheFunctionDomain n+3(2n-1)+4
We multiply parentheses
n+6n-3+4
We add all the numbers together, and all the variables
7n+1
Back to the equation:
-(7n+1)
10n-7n-1-7=0
We add all the numbers together, and all the variables
3n-8=0
We move all terms containing n to the left, all other terms to the right
3n=8
n=8/3
n=2+2/3
| 4(-9-2x=-68 | | 6y−3=15 | | 10=c/15 | | 5-3x=3-5x= | | x/4+62=36 | | y5=9 | | a+24=5(1+4a) | | 18-2n=22 | | 5+3x=3-5x= | | 10(-x+9)=-10 | | x+12+145=180 | | 4x7=6x+1 | | 4x/2=18 | | x+10=2(5+x) | | 7z+6=5z-10 | | w+3/8=11/6 | | 2p=8/32 | | −ퟑ풚=−ퟔퟒ+5y | | 6-10m=27.46 | | 10(t+3)=-30 | | r=15=27 | | 7x-5(6)=-22 | | (-2)(x+6)=-2x-12 | | 4(3x=4)-2x | | 18x^2-2x=0 | | 8(w-4)=-16 | | 3x+90=125 | | (2x+4)+(3x-49)=180 | | (10x+9)/5=(6-4x)/5 | | -5+2n+6=3 | | 4x-1+5=4x+3 | | 15y=-9 |